The mediating effects of gestational diabetes on fetal growth and adiposity in women who are overweight and obese: secondary analysis of the LIMIT randomised trial. (14th June 2018) - Poprzeczny, AJ; Louise, J; Deussen, AR; Dodd, JM
Abstract : Objective: To describe the mediating effect of maternal gestational diabetes on fetal biometry and adiposity measures among overweight or obese pregnant women. Design: Secondary analysis of the LIMIT randomised trial. Setting: Public hospitals, metropolitan Adelaide, South Australia. Population: Pregnant women with body mass index (BMI) ≥25 kg/m 2 and singleton gestation. Methods: Fetal ultrasound measures at 36 weeks of gestation and baseline BMI from women randomised to the LIMIT trial Standard Care group ( n = 912 women) were used to conduct causal mediation analyses using regression‐based methods. Main outcomes measures: Ultrasound measures of fetal biometry and adiposity at 36 weeks of gestation. Results: Increased maternal BMI was associated with increased measures of fetal head circumference [direct (unmediated) effect 0.18 (95% CI: 0.05–0.31), P = 0.005; total effect 0.17 (95% CI: 0.02–0.31), P = 0.018], abdominal circumference [direct effect 0.26 (95% CI: 0.11–0.41), P = 0.001; total effect 0.26 (95% CI: 0.11–0.42), P = 0.001] and estimated fetal weight [direct effect 0.22 (95% CI: 0.08–0.35), P = 0.002; total effect 0.22 (95% CI: 0.08–0.35), P = 0.002], with no evidence of mediation by treated gestational diabetes. There was no apparent association between maternal BMI and fetal adiposity measures, or mediation by treated gestational diabetes. Conclusions: We show an important association between increased maternal BMI and fetal growth, not mediated by treated gestational diabetes. There was no association between increased maternal BMI and fetal adiposity measures, or mediation by treated gestational diabetes. Whether these findings represent 'saturation' in the effect of maternal BMI on fetal growth or the effect of treatment of GDM is unclear. Funding: This project was funded by a 4‐year project grant from the National Health and Medical Research Council (NHMRC), Australia (ID 519240); The Channel 7 Children's Research Foundation, South Australia; and the US National Institutes of Health (R01 HL094235‐01). Tweetable abstract: Increased fetal growth associated with maternal obesity is not mediated by gestational diabetes. Tweetable abstract: Increased fetal growth associated with maternal obesity is not mediated by gestational diabetes.